Thymol-Loaded Biogenic Silica Nanoparticles in an Aquatic Environment: The Impact of Particle Aggregation on Ecotoxicity - Pereira, Iuri Barbosa; Carvalho, Endrew Henrique de Sousa; Rodrigues, Lais de Brito; Mattos, Bruno Dufau; Magalhaes, Washington Luiz Esteves; Leme, Daniela Morais [UNESP]; Krawczyk-Santos, Anna Paula; Taveira, Stephania Fleury; Oliveira, Gisele Augusto Rodrigues de [UNESP] (Wiley-Blackwell, 2021)
Thymol, a monoterpene phenol, is used as a natural biocide. To circumvent its chemical instability, we propose use of thymol-loaded biogenic silica nanoparticles (BSiO2#THY NPs); however, the toxicity of this system for aquatic organisms is unknown. Thus, the present study aimed to evaluate the toxicogenetic effects induced by thymol, BSiO2 NP, and BSiO2#THY on Artemia salina and zebrafish (Danio rerio) early life stages. We also investigated the impact of BSiO2 aggregation in different exposure media (saline and freshwater). Based on the median lethal concentration at 48 h (LC50(48h)), BSiO2#THY (LC50(48h) = 1.06 mg/L) presented similar toxic potential as thymol (LC50(48h) = 1.03 mg/L) for A. salina, showing that BSiO2 had no influence on BSiO2#THY toxicity. Because BSiO2 aggregated and sedimented faster in A. salina aqueous medium than in the other medium, this NP had lower interaction with this microcrustacean. Thus, BSiO2#THY toxicity for A. salina is probably due to the intrinsic toxicity of thymol. For zebrafish early life stages, BSiO2#THY (LC50(96h) = 13.13 mg/L) was more toxic than free thymol (LC50(96h) = 25.60 mg/L); however, BSiO2 NP has no toxicity for zebrafish early life stages. The lower aggregation of BSiO2 in the freshwater medium compared to the saline medium may have enhanced thymol's availability for this aquatic organism. Also, BSiO2#THY significantly induced sublethal effects as thymol, and both were genotoxic for zebrafish. In conclusion, although BSiO2#THY still needs improvements to ensure its safety for freshwater ecosystems, BSiO2 NP seems to be a safe nanocarrier for agriculture. Environ Toxicol Chem 2021;00:1-9. (c) 2020 SETAC
Keywords: Biocide delivery systems; Nanoparticles; Aggregation; Zebrafish; Artemia salina; Comet assay